1998
DOI: 10.1021/ef980012u
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conversion of Used Oil to Hydrocarbon Fuels in a Fractionating Pyrolysis Reactor

Abstract: Pyrolysis of used sunflower oil was carried out in the presence of different amounts of HZSM-5 at 400 and 420 °C in a reactor equipped with a fractionating packed column, the length of which was varied. The products consisted of gaseous and liquid hydrocarbons, acids, CO, CO 2 , water, and coke. The compositions of the gaseous and liquid products were studied by gas chromatography. The product yields and compositions were affected by catalyst content, temperature, and column length. Nearly complete conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 18 publications
2
39
0
5
Order By: Relevance
“…The aromatic content decreased with longer columns, believed to be caused by internal thermal effects between the liquid and vapor phases [16].…”
Section: Introductionmentioning
confidence: 98%
“…The aromatic content decreased with longer columns, believed to be caused by internal thermal effects between the liquid and vapor phases [16].…”
Section: Introductionmentioning
confidence: 98%
“…For example, it has been reported the production of hydrocarbons from Tung oil in China during the Second World War. 11 Since then, numerous studies about the thermal [12][13][14][15][16][17][18] and catalytic [19][20][21][22][23][24][25][26][27][28][29] pyrolysis of triglycerides and Vol. 20, No.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these oxygenated compounds are partially or completely reduced when the reaction is carried out in the presence of a catalyst. 8 For instance, it was observed that the presence of different types of zeolites dramatically changes the reaction products, 21,[24][25][26]28 affording essentially non-oxygenated compounds, mainly aromatic and short chain hydrocarbons in the range of gasoline. 19,22 On the other hand, it was also reported that the products of soybean and babassu oils pyrolysis catalyzed by γ-alumina doped with nickel and molybdenium were completely deoxygenated when the reaction was carried out in the presence of hydrogen pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Por exemplo, a desoxigenação dos produtos da decomposição térmica de óleo de soja é favorecida quando a reação é realizada na presença de diferentes zeólitas, [58][59][60] sendo também observado que reações de craqueamento da cadeia dos hidrocarbonetos formados, ciclizações e aromatização levam à formação de um produto próximo à faixa da gasolina (8-10 carbonos). Já aluminossilicatos não estruturados e (γ-alumina) 61,62 são também eficientes na desoxigenação dos produtos formados, diminuindo as reações de craqueamento da cadeia carbônica e de ciclização e aromatização, gerando um biocombustível com perfil de destilação próximo ao do diesel. Por outro lado, foi relatado que alguns catalisadores, como óxidos básicos MgO e CaO 59 ou Nb 2 O 5 63 e alguns derivados, 64 estabilizam os ácidos carboxílicos formados levando a produtos com acidez superior à verificada no craqueamento térmico.…”
Section: Processos De Obtenção De Hidrocarbonetos: Bio-óleounclassified